Conversational Style of Male and Female Characters in Game of Thrones Season 8 - Tati Khumairoh; Mirjam Anugerahwati (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This study aims to find out what are conversational features used by male and female characters in Game of Thrones season 8, how it is represented in their conversation, and how power and social status affect characters' linguistic behavior. This study used a descriptive qualitative research design. The data of this study are twenty-two conversations taken from episode 1 up to episode 6 of season 8. There are four conversational style features discussed in this study: (1) talkativeness, (2) interruption, (3) compliments, and (4) minimal responses. The results show that all four features are found in the conversations, but they are manipulated differently by male and female characters. Also, the use of gender conversational style features in this case seems universal. Female characters are more talkative which confirms the theory of women’s language. Male characters also use female conversational style more frequently in terms of minimal responses and compliments. However, power plays an important role in this case since it enables characters to be more dominant which reflects that gender is not the only factor to control the conversation. Keywords: compliments, conversational style, interruptions, minimal response, talkativeness Abstrak: Penelitian ini bertujuan untuk mengetahui gaya percakapan yang digunakan oleh pemeran pria dan wanita dalam serial berjudul Game of Thrones Season 8, bagaimana gaya tersebut direpresentasikan dalam percakapannya, dan bagaimana kekuasaan dan status sosial mempengaruhi perilaku linguistik karakter. Penelitian ini menggunakan desain penelitian deskriptif kualitatif. Data dalam penelitian ini adalah dua puluh dua percakapan yang diambil dari episode 1 hingga episode 6 di season 8. Ada empat fitur gaya percakapan yang dibahas dalam penelitian ini: (1) tingkat keaktifan berbicara, (2) interupsi, (3) pujian, dan (4) tanggapan minimal. Hasil penelitian menunjukkan bahwa keempat fitur ditemukan dalam series ini, namun dipraktekkan secara berbeda oleh karakter pria dan wanita. Selain itu, penggunaan fitur gaya percakapan gender dalam hal ini terkesan universal. Karakter perempuan lebih banyak bicara yang mana mendukung teori gaya bahasa wanita. Karakter pria juga lebih sering menggunakan gaya percakapan wanita dalam hal memberikan tanggapan minimal dan pujian. Namun, kekuasaan memainkan peran penting dalam hal ini karena memungkinkan karakter lebih dominan dan menjelaskan bahwa gender bukan satu-satunya faktor yang mengendalikan percakapan. Kata kunci: gaya percakapan, interupsi, respon minimal, pujian